Abration Analysis of Tuapeijat Coastal in Area North Sipora Sub-district of Kepulauan Mentawai Reqency - Suryanti, IRA; Juita, S.Pd. M.Si, Erna; S.Si. M.Sc, Farida (STKIP PGRI Sumbar, 2014)
ABSTRACT This research aim is to analyse (1) coastal characteristics (2) Waving characteristics (3) Accelerating of transport sediment (4) Determination of Abration, acretion, or well-balanced Coastal in Area North Sipora Sub-district of Kepulauan Mentawai Reqency. This Research type is quantitative descriptive research. Source of data are primary data andsecondary data. Intake of this research sample using purposive sampling, pursuant to storey;level of abrasi perceived and happened coastal Alongside Tuapeijat that is three of (3) sampel that is Coast Teak;Core, Coastal of Mapaddegat, Coastal of Berimanua. Technique analyse data the used equation for the calculation of wavelength, wave velocity, energi waving is, high of flinging down waving, accelerateing to transport sediment, and determinant of abrasi, akresi or is well-balanced. Based on data analysis of field, obtained that 1) Coastal Characteristics like Coast Teak;Core have sloping coastal characteristic, coastal Later;Then Mapaddegat have Coastal and surging coastal characteristic of Betumonga have precipitous coastal characteristic 2) Characteristics of Waving that is Mean wavelength equal to 37,99 metre, Mean wave velocity equal to 7,64 metre / second, mean of Energi waving equal to 7,17 singk / dt2, High mean of flinging down waving equal to 1,51 metre 3) Fast Value Transport Sediment that is: Fast mean transport sediment equal to 262,87 m3 / day 4) Determinant Waving or Coastal Dynamics that is, pursuant to result of research can know phenomenon that happened in Coast of Tuapeijat District Of Sipora North Sub-Province Archipelago of Mentawai that is phenomenon of Akresi. Phenomenon of Akresi happened at Coast Teak;Core with value of Go equal to 4,04, Coast of Mapaddegat with value of Go equal to 9,21, Coast of Betumonga with value of Go equal to 0,08. Pursuant to direct perception and calculation field can be concluded that coastal Alongside Tuapeijat District Of Sipora North Sub-Province Archipelago of natural Mentawai of akresi